Overcoming Breast Cancer Drug Resistance: A Novel Approach Using siRNA-Mediated P-glycoprotein Downregulation to Enhance Vinorelbine Efficacy - Zahra Abbasfard; Abbas Behzad-Behbahani; Banafshe Rastegari; Sirous Naeimi; Mehdi Moghanibashi; Fatemeh Safari (Advanced Pharmaceutical Bulletin, 2024)
Purpose: Cancer, the second leading cause of mortality worldwide, represents a global health challenge, primarily due to drug resistance. Vinorelbine is a chemotherapeutic agent that disrupts cancer cell growth by targeting microtubules and inducing apoptosis. However, drug resistance remains a formidable obstacle. This resistance is caused by various factors including genetic mutations, drug efflux mechanisms, and DNA repair systems. Resolution of this challenge requires an innovative approach. This study investigated the potential of small interfering RNA (siRNA) to target and downregulate a vinorelbine-resistant MCF-7/ADR breast cancer cell line. Methods: Cells were cultured in Dulbecco’s modified Eagle’s medium (DMEM) 10% fetal bovine serum/penicillin/streptomycin. An siRNA targeting ABCB1 was designed and synthesized, and the cells were transfected with siRNA at final concentrations of 10, 20, and 30 nM. The3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assay was used to assess cell viability. ABCB1 mRNA expression levels were determined by real-time polymerase chain reaction (PCR). Results: MCF-7 cells exhibited a higher sensitivity to vinorelbine than MCF-7/ADR cells. MCF-7/ADR cells exhibited resistance to vinorelbine at concentrations, 12.50 and 25.00 μM. Treatment with siRNA significantly reduced ABCB1 expression by 2.93-fold (P=0.0001). Similarly, co-treatment with siRNA and vinorelbine produced a substantial 2.89-fold decrease in ABCB1 gene expression in MCF-7 cells compared to that in MCF-7/ADR cells (P=0.0001). Conclusion: The results of the present study indicate that the concurrent use of siRNA and vinorelbine holds substantial promise as a therapeutic approach to overcome ABCB1-mediated multidrug resistance (MDR) in breast cancer. It is necessary to conduct comprehensive clinical trials to determine the true effectiveness of this combination therapy.